APATITE-CARBONATE ERUPTIVE BRECCIAS OF THE TOMTOR PLUTON. A NEW TYPE OF ROCK IN CARBONATITE COMPLEXES - Bagdasarov Yu.A. (My University, 1990)
Previously undiscovered rocks of apatite-carbonatite (ferrodolomite-calcite) composition and typically brecciated structure, intruding earlier calcite carbonatites and characterized by a distinctive set of minerals in the composition of their inclusions have recently been found in the Tomtor pluton (on the right bank of the Anabar River, northwestern Yakutia). At least half of the total vast area of development of carbonatites and intensively carbonatized ultramafic and alkalic rocks, amounting to about 35 km2, consists of blocks (relicts) of rocks of picritic composition, which were encountered in almost every borehole both in the carbonatites themselves and in the weathered layers overlying them. Extrusive-eruptive manifestations were also widespread in the carbonatite stage, especially in the western part of the carbonatite stock. The breccia cement consists of a fine- and medium-grained rock consisting of calcite and ferrodolomite with variable, but on the whole almost equal amounts of both, plus apatite grains 0.1-0.5 mm long, which sometimes also have the character of inclusions in the carbonatite cement.